Transfer Juridical Review of Rental Object Function in A Rental Agreement to Rent a Shop House (Ruko) based on the Good Faith Principle - Semiyanto Semiyanto; Siti Ummu Adillah; Maryanto Maryanto; Lathifah Hanim (Sultan Agung Notary Law Review, 2022)
The purpose of this study was to find out the juridical review regarding the transfer of the function of the object of the shop house rental based on the principle of good faith. The research methodology used is normative juridical with secondary data sources. The results showed that the standard of good faith in the shop house rental agreement (ruko) was carried out before and after the implementation of the agreement. Prior to the implementation of the agreement in the form of honesty and openness, while the objective of good faith in the lease agreement is the fulfillment of achievements in the implementation of the agreement. Regarding the transfer of the function of the object for renting a shop house (ruko) to other than the original purpose, which was legally agreed upon, the Civil Code does not explicitly regulate but the transfer of the function of the object for renting a shop house (ruko) can be seen in the provisions of Article 1560 of the Civil Code where the tenant is obliged to maintain and care for the rented house properly. . Then in Article 1561 of the Civil Code that tenants are prohibited from using the leased object for purposes other than its purpose. These two provisions serve as points for interpreting that the transfer of the object of lease that causes damage is not permitted. 201/Pdt.G/2015/PN Dps regarding the judge's interpretation of the existence of a default in the dispute over the object of the lease from which losses arise due to the use of a shop house (ruko) outside the agreement.